(untitled) (Manila, 1934)
Contents: Review of Philippines progress; Sketches of the lives of delegates to the constitutional leaders; Critical appreciation of the lives and labors of filipino leaders; Sketches of the lives of members of the tenth Philippine legislature...
Keywords: Philippines,Philippines; Chính trị và chính phủ,Politics and government